Analysis of Fiber Content, Reduced Sugar and Organoleptic Quality of Nata De Avocado on The Concentration Variations of Lime Juice and Mung Bean Extract - Fikriansyah, Ibnu Zulfan; Suryani, Titik (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The purpose of this study was to determine the content of fiber, reducing sugar and organoleptic quality of nata de avocado on the concentration variations of lime juice and mung bean extract. This research method was an experiment with Completely Randomized Design (CRD), two factors. The first factor was lime juice 2.4% of the medium volume (6ml/250ml)/J1 and lime juice 2.8% of the medium volume (7ml/250 ml)/J2. The second factor was mung bean extract 20% of the medium volume (50ml/250 ml)/H1 and mung bean extract, 25% of the medium volume (62.5ml/250 ml)/H2 and nata de coco as a control. Organoleptic quality testing included color, texture, aroma, and acceptability carried out 25 respondents. The results showed the best content of fiber, reducing sugar and organoleptic quality of nata de avocado were 4.45%, 13.425%, white in color, chewy texture, non-sour aroma and quite likes in J2H1 treatment (2.8% of lime juice + 20% of mung bean extract).